Role of active control in increasing base pressure at Sonic Mach Number - G. M, Fharukh Ahmed; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
Use of microjets as an active control mechanism to control the base pressure in suddenly expanded flow from the C-D nozzle exhausted to the duct is investigated in this article. Experimental analysis is carried out at sonic Mach number and different nozzle pressure ratios. The enlarged diameter used in this investigation is 16 mm, 22.5 mm, and 27.5 mm. The length and diameter of the duct where the flow expands are also varied during the analysis. The role played by four micro jets of 1 mm diameter as an orifice to regulate the base pressure. The results as the percentage increase in base pressure are plotted for different level expansion and area ratio. For higher NPR = 7, the control significantly increases the base pressure without disturbing the wall pressure distribution. L/D = 3 and 4 seems to be optimum in resulting in a maximum increase in base pressure. For lower area ratio the minimum duct length required is L/D =3, whereas for the highest area-ratio this limit is L/D =4.